The Impact of Innovation Climate & Job Satisfaction on Corporate Entrepreneurship - Farrukh, Muhammad; Iqbal, Shahid; Tanzila,; Khan, Ikram (Journal of Asian Business Strategy, 2014)
This study verified corporate entrepreneurship, innovation climate and Job satisfaction (person-job fit, Salary Benefit) as the research framework. Through a literature review, we examined causal relationship among these variables. The climate for innovation is demonstrated by team unity, administrative encouragement, resources, independence, as well as openness to innovation. Recent studies have showed a lack of research in conventional mechanized firms on innovative climate. The relationship model was examined with regression analysis, and all hypotheses established support. This result implied that climate for the innovation enhanced corporate entrepreneurship.